Security Challenges and the Conduct of Legislative Process in Nigeria: The Case of 8th National Assembly - Onyendinachi Iheanacho; Glory Edim Inok; Etim Edet Okon Ubokuloh (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
This study examines the relationship between security challenges and the conduct of legislative processes in Nigeria, with a particular focus on the 8th National Assembly (2015–2019). The paper provides conceptual clarifications of key terms and presents an overview of Nigeria's security challenges before specifically analysing security incidents that confronted the 8th National Assembly and their legal implications. Notable security issues examined include the theft of the Senate mace, the blockade of the residences of the Senate President and Deputy Senate President, and the invasion of the National Assembly complex by operatives of the Department of State Security Services. Furthermore, the study evaluates the challenges of lawmaking in an insecure environment to determine whether the quality of legislation enacted during periods of insecurity is adversely affected. The findings reveal a direct correlation between insecurity and poor legislative outcomes. The paper concludes by recommending that excessive interference by the executive arm in the affairs of the National Assembly should be curtailed. Additionally, the National Assembly security architecture should be restructured to place Special Forces in charge of protecting legislative personnel and facilities.